USABILITY APLIKASI ANDROID HONDA e-Care DENGAN USE QUESTIONNAIRE DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Kudiantoro Widianto (Jurnal Poli-Teknologi, 2020)
Honda Pondok Pinang, which is located on Jl. Ciputat Raya No.80 Pondok Pinang, South Jakarta, in customer service using an android application called HONDA e-Care. HONDA e-Care is very helpful in making it easier for consumers to access Honda service services. Customers can book services at Honda dealers online, get notifications of periodic maintenance schedules, and search for the nearest dealer from a location that can be seen on a digital map by first accessing the Honda e-Care application. But consumers often also face problems, such as when booking a service, but the ongoing booking service does not appear. Until now, no one has conducted research on the quality of the Honda e-Care application. This study aims to measure the extent of the usability of the HONDA e-Care android application and provide suggestions for developing the HONDA e-Care application in the future. Based on the gap analysis, it was found that in general the HONDA e-Care android application on the Honda Pondok Pinang was not satisfied with the quality of the current applications. Based on the IPA analysis, the priority scale for improving the quality of the HONDA e-Care android application can be mapped where quadrant I is the highest priority scale according to the user's perspective, namely: [2], [5], [7], [8] and [9]. These four items must be upgraded immediately by the manager to meet user expectations.